Analysis of Government Policy in Responding to the Economic Recession Due to Covid-19 in Indonesia - Mukaromah, Haniatul (Journal of Economics and Social Sciences (JESS), 2023)
Introduction/Main Objectives: This study aims to determine fiscal policy in dealing with the economic recession due to Covid-19 in Indonesia. Research Methods: This study uses qualitative methods and a library research approach. Finding/Results: This study's results prove that fiscal policy's role is vast in helping to deal with the economic recession in Indonesia due to Covid-19. The Government succeeded in implementing fiscal policy on state revenues and expenditures to maintain economic growth and economic stability. Fiscal policies implemented by the Government to improve the Indonesian economy during the pandemic, including refocusing and revising the 2020 State Budget as an efficiency measure for state spending, rearranging the allocation of state revenues in the 2020 State Budget, a tax incentive program to relieve taxpayers, revising tax revenue targets, and implementing digital taxes for activities through electronic media. Fraud is still found in these policies, so the Government needs to re-evaluate. Conclusion: This study is expected to become the latest source of information for those who need it in the future.